'I hate visual culture.' The controversial rise of visual studies and the disciplinary politics of the visible. Issue 4 (7th August 2020) - Boidy, Maxime; Patarin-Jossec, Julie; Hansen, Susan
Abstract : The rise of Visual Studies in the American academy during the 1990s is part of an after-effect of the institutionalisation of Cultural Studies in the United States. It specifically implies a decentring of the discipline of art history towards the interdisciplinary study of sociocultural visibilities. This paper deals with the development of this research field in an intellectual climate still characterised by the 'Culture Wars' engaged in by the neoconservatives against certain areas of the academy and the artistic world during the 1980s. By taking into account the struggles about Visual Studies inside the intellectual Left as an integral part of their definition, this paper analyses the academic politicisations of the notions of 'Visual Culture' ( culture visuelle ) and 'Visual Studies' ( études visuelles ) in the context of the current French importation and redefinition of these categories.